2022
DOI: 10.1155/2022/2913942
|View full text |Cite
|
Sign up to set email alerts
|

Application of the Slope Coefficient of the Equivalent M–C Criterion in Layered Rock Mass Engineering

Abstract: The slope coefficient ω is defined based on the insufficiency of the area equivalent method, the slope of the equivalent M–C criterion obtained from the instantaneous equivalent, and the optimal first-order approximation to reduce the error between the simulated value and the measured value of the surrounding rock and ensure the safety of the project. Different ω conditions are set to obtain multiple equivalent M–C strength parameter combinations. The above combinations are input to the ubiquitous joint model … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…Hoek-Brown proposed that the anisotropic rock strength parameters vary depending on the load direction. When studying the anisotropic rock strength, it has been revealed that the Hoek-Brown criterion parameters quantify the anisotropic effect [26]- [28].…”
Section: Introductionmentioning
confidence: 99%
“…Hoek-Brown proposed that the anisotropic rock strength parameters vary depending on the load direction. When studying the anisotropic rock strength, it has been revealed that the Hoek-Brown criterion parameters quantify the anisotropic effect [26]- [28].…”
Section: Introductionmentioning
confidence: 99%